2015
DOI: 10.1080/13674676.2014.1003169
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering, religiosity and well-being: interrelationships among Australian churchgoers

Abstract: Existing research has mostly found positive, but sometimes inconclusive and contradictory, results about the relationships between volunteering and well-being, as well as between church attendance and volunteering. This paper aims to clarify how volunteering and religious beliefs and practices are related to well-being among Christian churchgoers. Utilising data from the 2011 Australian National Church Life Survey, volunteering was found to partially mediate the positive relationship between religiosity and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Religiosity In prior studies, people with strong religious beliefs have, on average, reported feeling happier than others (Abdel-Khalek 2011; Clark and Lelkes 2005;Lechner and Leopold 2015;Mollidor et al 2015). This is confirmed in the present analysis: the respective variable's coefficient had a positive sign and was statistically significant in all three models, as shown in Table 2.…”
Section: Multilevel (Mixed Effects) Full Modelsupporting
confidence: 86%
“…Religiosity In prior studies, people with strong religious beliefs have, on average, reported feeling happier than others (Abdel-Khalek 2011; Clark and Lelkes 2005;Lechner and Leopold 2015;Mollidor et al 2015). This is confirmed in the present analysis: the respective variable's coefficient had a positive sign and was statistically significant in all three models, as shown in Table 2.…”
Section: Multilevel (Mixed Effects) Full Modelsupporting
confidence: 86%
“…Moreover, volunteering was a source of pride and satisfaction. Mollidor, Hancock, and Pepper () found some support for a partially mediating effect of volunteering between religiosity and wellbeing among Australian churchgoers. They used a large survey sample to show that some religious denominations prompted more volunteering, which subsequently improved a person's wellbeing (i.e., general satisfaction).…”
Section: Benefits Of Volunteeringmentioning
confidence: 99%
“…Protestant, Catholic, and other religious denomination). The variables included in the PSM model were chosen because they are known correlates of volunteer participation and wellbeing (Mollidor et al 2015;McDougle et al 2013;Taniguchi and Thomas 2011).…”
Section: Participantsmentioning
confidence: 99%